2011
DOI: 10.3406/paleo.2011.5427
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Perspectives: Sourcing Epi-Palaeolithic to Chalcolithic Obsidian from the Öküzini Cave (SW Turkey)

Abstract: Fifty-six pieces of obsidian from the Öküzini Cave in SW Anatolia were elementally characterised using particle induced X-ray emission [PIXE], the artefacts coming from strata that span the early Epi-Palaeolithic to Late Chalcolithic. The obsidian comes from two sources in southern Cappadocia, East Göllü Dağ and Nenezi Dağ (380 km distant), representing the earliest evidence for these sources' use at distance. The cave's inhabitants perpetually existed on the margins of those socioeconomic networks responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…East Gollu Dag and Nenezi Dag products are attested in early Epi-Palaeolithic strata at the Okiizini and Karain Caves of the Antalya region, dated to the late 17th/early 16th millennia BC (Renfrew et al 1966: 42-43;Carter et al in prep. ), while the former obsidian is also known from late Epi-Palaeolithic sites of the middle Euphrates and southern Levant dating to 12,000-10,000 BC ( fig.…”
Section: Is It True That Catalhoyiik Controlled the Obsidian Trade?mentioning
confidence: 97%
“…East Gollu Dag and Nenezi Dag products are attested in early Epi-Palaeolithic strata at the Okiizini and Karain Caves of the Antalya region, dated to the late 17th/early 16th millennia BC (Renfrew et al 1966: 42-43;Carter et al in prep. ), while the former obsidian is also known from late Epi-Palaeolithic sites of the middle Euphrates and southern Levant dating to 12,000-10,000 BC ( fig.…”
Section: Is It True That Catalhoyiik Controlled the Obsidian Trade?mentioning
confidence: 97%
“…Furthermore, a more complete understanding from the archeometric point of view may be reached only if in the future we are able to work on more geological sources using the same methods. Indeed it has been shown that it is necessary, especially when we are dealing with several sources showing closed but distinct compositions, to first established a source database to discuss the questions of provenance (Carter et al, 2008(Carter et al, , 2011Poupeau et al, 2010).…”
Section: Obsidian Sourcingmentioning
confidence: 99%
“…A handful of pieces of central Anatolian obsidian have been identified in late EpiPaleolithic (post-glacial) assemblages from Ö kü zini cave near Antalia (more than 300 km away) (Carter et al 2011), demonstrating that people did sometimes visit the Gö llü Dag area during the terminal Pleistocene, but the human presence may have been so ephemeral that it is difficult to detect. To date only two sites with definite late Epi-Paleolithic layers have been identified and investigated in central Turkey (Arbuckle and Erek 2012;Baird et al 2013).…”
Section: Discussionmentioning
confidence: 99%